Dynamic Relationship of Macro Variables and Liquefied Petroleum Gas Subsidy Transformation Program - Eddy Prabowo; Harianto Harianto; Bambang Juanda; Dikky Indrawan (Bina Nusantara University, 2023)
Most Indonesians rely on liquefied petroleum gas as one of their primary sources of energy. Liquefied petroleum gas is classified into subsidized and non-subsidized. Subsidized liquefied petroleum gas is primarily used by low-income households, small businesses, as well as poor fishermen and farmers for cooking. However, no exit strategy has been established to overcome the increase in government spending on subsidized kerosene introduced in 2008. The problem is that macro variables may influence liquefied petroleum gas economic prices. The research aimed to identify the relationship between macro variables that might affect liquefied petroleum gas economic prices. It applied a quantitative method with Vector Auto Regression (VAR) and Vector Error Correction Model (VECM). The results demonstrate that inflation rate have a significant impact on the economic price of liquefied petroleum gas. Then, gross domestic product, inflation rate, and world gas price have positive correlations to the economic prices in liquefied petroleum gas. Meanwhile, currency exchange and world oil price have negative coefficients. The regression model indicates that a rise in inflation increases market prices in liquefied petroleum gas. Furthermore, the increased subsidized fuel means more poor people cannot afford liquefied petroleum gas. It is because high inflation reduces purchasing and potentially increases the number of poor people.